The First Cbk-Like Phage Infecting Erythrobacter, Representing a Novel Siphoviral Genus - Li, Xuejing; Guo, Ruizhe; Zou, Xiao; Yao, Yanyan; Lu, Longfei (Frontiers in Microbiology, 2022)
Erythrobacter is an important and widespread bacterial genus in the ocean. However, our knowledge about their phages is still rare. Here, a novel lytic phage vB_EliS-L02, infecting Erythrobacter litoralis DSM 8509, was isolated and purified from Sanggou Bay seawater, China. Morphological observation revealed that the phage belonged to Cbk-like siphovirus, with long prolate head and long tail. The host range test showed that phage vB_EliS-L02 could only infect a few strains of Erythrobacter, demonstrating its potential narrow-host range. Genome size of vB_EliS-L02 was 150,063 bp with a G+C content of 59.43 %, encoding 231 putative open reading frames (ORFs), but only 47 were predicted to be functional domains. Fourteen auxiliary metabolic genes were identified, including phoH that may confer vB_EliS-L02 the advantage on regulating the phosphate uptake and metabolism under a phosphate limiting condition. Genomic and phylogenetic analysis indicated that vB_EliS-L02 was the most closely related to genus Lacusarxvirus with low similarity (shared genes <30%, and average nucleotide sequence identity <70%), distantly from other reported phages, and could be grouped into a novel viral genus cluster, here as Eliscbkvirus. Meanwhile, genus Eliscbkvirus and Lacusarxvirus stand out from other siphoviral genus and could represent a novel subfamily within Siphoviridae, named as Dolichocephalovirinae-II. Being a representative of an understudied viral group with manifold adaptations to the host, phage vB_EliS-L02 could improve our understanding about the virus-host interactions and provide reference information for viral metagenomic analysis in the ocean.